Providing an enabling environment to promote the Sustainable Development Goals: Coventry University's experience [version 1; peer review: 2 approved] - Jaliyyah Bello; Mojtaba Ammari-Allahyari; Selina Fletcher (Emerald Publishing, 2020)
Higher Education Institutions provide a vital role in providing education towards solving sustainability issues. Hence, the adoption of development agendas, such as the United Nations Sustainable Development Goals (SDGs) through the SDG Accord, into curriculum. As a signatory of the sector SDG Accord, Coventry University Group has the responsibility of providing an enabling environment to promote the achievement of the Goals. This article introduces a model for embedding the goals into curriculum; with creative teaching practice and enriching student experience at the centre to the approach taken. The approach considers three dimensions: Staff Development, the Goals within Teaching, and Students' Activities.